2013
DOI: 10.1590/s0102-09352013000600001
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters of dairy goats submitted to estrus synchronization with prostaglandin F2α associated or not to hCG at estrous onset

Abstract: The objective of this study was to evaluate the efficiency of two doses of PGF associated or not to hCG on the associated reproductive parameters in dairy goats. A total of 29 goats received two doses of 30μg d-cloprostenol latero-vulvar at a 10 day intervals (Day 1 and Day 10). The does were allocated according to body weight and body condition score into two treatments, to receive hCG (250IU) or saline at estrus onset. After the second dose of PGF, estrus was monitored and ultrasound exams were performed twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
4
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
4
7
4
3
Order By: Relevance
“…Fonseca et al (2008) also noted that 73.8% of the goats were first observed in estrus in the morning and suggested that in goats, the estrus is predominantly a nightly phenomenon. Likewise, Esteves et al (2013) observed a 91% occurrence of night estrus and a 9% occurrence of day estrus. On the other hand, the 11.5-day protocol evoked estrus predominantly during the day (66.7% first detected at the end of the afternoon) in first trial and in the night (54.8%) in second trial.…”
Section: Parametermentioning
confidence: 87%
See 3 more Smart Citations
“…Fonseca et al (2008) also noted that 73.8% of the goats were first observed in estrus in the morning and suggested that in goats, the estrus is predominantly a nightly phenomenon. Likewise, Esteves et al (2013) observed a 91% occurrence of night estrus and a 9% occurrence of day estrus. On the other hand, the 11.5-day protocol evoked estrus predominantly during the day (66.7% first detected at the end of the afternoon) in first trial and in the night (54.8%) in second trial.…”
Section: Parametermentioning
confidence: 87%
“…The growth follicular rate in goats is near to of 1 mm/day (Menchaca et al, 2007). It means that for T 7 goats, follicles could reach the ovulatory diameter (Esteves et al, 2013) and adequate estradiol production in three to four days after second d-cloprostenol injection. Goats from T 10 and T 11.5 were more likely in a regression phase in which smaller follicles could originate ovulatory follicles, indicating more time needed to reach ovulatory diameter and estrus onset.…”
Section: Parametermentioning
confidence: 97%
See 2 more Smart Citations
“…Improvements in the design of oestrus induction protocols have allowed to expand the out-of-season use of artificial insemination, inseminating goats at specific times, while achieving pregnancy rates comparable to those obtained with the use of visual detection of oestrus (Menchaca & Rubianes 2004;Simoes 2015). Common protocols to induce oestrus in acyclic goats include the combined or single use of gonadotropins, gonadotropin-releasing hormone (GnRH), progestins and prostaglandins (Esteves et al 2013;Contreras-Villarreal et al 2016;Sen & Onder 2016).…”
Section: Introductionmentioning
confidence: 99%